Cytoreductive surgery and hyperthermic intrathoracic chemotherapy in thymic epithelial tumors with pleural spread or recurrence: a prospective, single-arm, phase II study - Shuai Wang; Xinyu Yang; Jiahao Jiang; Fei Liang; Yuansheng Zheng; Yongqiang Ao; Jian Gao; Hao Wang; Lijie Tan; Jianyong Ding (Nature Communications)
Abstract Pleural spread or recurrence of thymic epithelial tumors (TETs) is a tricky puzzle in the clinic and there is currently no recognized effective treatment. This trial evaluated the safety and efficacy of cytoreductive surgery and hyperthermic intrathoracic chemotherapy (S-HITOC) for TETs with pleural spread or recurrence. Here, we reported short-term outcomes of enrolled 45 patients receiving S-HITOC with 25 mg/m2 doxorubicin and 50 mg/m2 cisplatin. The pleural tumor index (PTI) has been proposed for evaluating pleural tumor burden. Treatment-related adverse events of grade ≥3 occurred in eight (17.8%) patients. The pain Visual analog scale (VAS) score was 5.4 ± 1.9 on the 1st day after treatment and was similar to that at baseline level on the 7th day after treatment (p = 0.218). There was no significant difference in the quality of life score (p = 0.676) between baseline and the 60th day after treatment. The estimated 2-year PFS and OS rates were 82.8% and 100.0%, respectively. Subgroup analyses revealed that patients with PTI scores >10 had worse PFS than those with PTI scores ≤10 (p < 0.001). S-HITOC had a manageable complication rate. Early clinical outcomes confirmed that S-HITOC offers encouraging oncological benefits for TETs and satisfactory control of myasthenia gravis. Trial number: NCT05446935.